ANALYSIS OF THE REQUIREMENTS OF THE SPINNING ENTERPRISES OF UZBEKISTAN AND THE WORKING CONDITIONS IN IT (World Economics and Finance Bulletin, 2024)
This article investigates the current state and future prospects of spinning enterprises in Uzbekistan, with a particular focus on labor conditions. The study explores various aspects of the spinning industry, evaluates existing labor conditions, and provides recommendations for improvements. Using a combination of literature review, field studies, and statistical analysis, this research aims to provide a comprehensive overview of the challenges and opportunities facing Uzbekistan's spinning sector
Keywords: Uzbekistan; spinning enterprises; labor conditions